International Youth Integration at the Eurasian Space - Ivan Igorevich Esipov (Управленческое консультирование)
In today’s world the processes of integration of the various countries are of growing importance. Such processes mainly take place in regions, which have shared economic, cultural, ethnic, ideological, religious or linguistic community. Development of integration, as such, without the support of the citizens of the states, which take part in integration is possible only to a certain extent. We can say that each integrative group has its own purpose and ideology.